2007
DOI: 10.1186/1472-6807-7-35
|View full text |Cite
|
Sign up to set email alerts
|

High resolution crystal structure of PedB: a structural basis for the classification of pediocin-like immunity proteins

Abstract: Background: Pediocin-like bacteriocins, ribosomally-synthesized antimicrobial peptides, are generally coexpressed with cognate immunity proteins in order to protect the bacteriocinproducer from its own bacteriocin. As a step for understanding the mode of action of immunity proteins, we determined the crystal structure of PedB, a pediocin-like immunity protein conferring immunity to pediocin PP-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…For each class IIa bacteriocin encoded in a genome there is a one to one relationship between bacteriocin and cognate immunity protein; whereas, in contrast, for each pair of class IIb two-peptide bacteriocins there is a single cognate immunity protein encoded in a genome [ 9 ]. Structures of five immunity proteins have already been solved: ImB2 [ 19 ], EntA-im [ 20 ], PedB [ 21 ], PisI [ 22 ], and Mun-Im [ 23 ], all protective against IIa bacteriocins. As yet, no structures for immunity proteins protective against IIb or IIc bacteriocins have been solved.…”
Section: Introductionmentioning
confidence: 99%
“…For each class IIa bacteriocin encoded in a genome there is a one to one relationship between bacteriocin and cognate immunity protein; whereas, in contrast, for each pair of class IIb two-peptide bacteriocins there is a single cognate immunity protein encoded in a genome [ 9 ]. Structures of five immunity proteins have already been solved: ImB2 [ 19 ], EntA-im [ 20 ], PedB [ 21 ], PisI [ 22 ], and Mun-Im [ 23 ], all protective against IIa bacteriocins. As yet, no structures for immunity proteins protective against IIb or IIc bacteriocins have been solved.…”
Section: Introductionmentioning
confidence: 99%
“…The four-helix bundle fold found for LciA is similar to the fold observed for the immunity proteins of the pediocin-like bacteriocins. Interestingly, LciA and the pediocin-like immunity proteins function in a similar manner. They bind to the bacteriocin–man-PTS complex and prevent membrane leakage .…”
Section: Resultsmentioning
confidence: 53%
“…By generating hybrid immunity proteins in which the C- and N-terminal parts were derived from different immunity proteins, it has been shown that the C-terminal halves of the immunity proteins of the pediocin-like bacteriocins are responsible for recognition of the cognate bacteriocin and receptor complex. , Furthermore, mutational studies of Mun-im and PedB have indicated that the unstructured C-terminal ends of these pediocin-like immunity proteins are important for immunity. To investigate the role of the unstructured C-terminal tail of LciA, point mutations were introduced at the C-terminal end and three truncated variants of LciA were constructed (deletion of 2, 6, or 10 residues from the C-terminal end).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Many studies have been focused on isolation and genetic manipulations these genes in different strains suitable for industrial applications via genetic engineering [17,18].…”
Section: Detection Of Papa and Pedb Genesmentioning
confidence: 99%